Case Report: Premature lactation in Jersey heifers after intercontinental air transport - Liu, Guanglei; Done, Eryl; Ip, Joyce; Li, Cheuk Ming; Flay, Kate; Kenéz, Ákos (Frontiers in Veterinary Science, 2025)
The establishment of a new teaching and research dairy farm at City University of Hong Kong (Hong Kong SAR, China) necessitated the importation of pregnant dairy heifers from Australia. On 20 September 2022, a cohort of 24 pregnant heifers arrived by air to CityU Farm. Commencing shortly after arrival, during the subsequent month all heifers exhibited abnormal udder development resembling cows within 2 weeks pre-parturition, despite being 10–17 weeks from calving. Further clinical examination showed excessive teat edema, ventral abdominal edema and milk leakage. Additionally, serum biochemical analysis identified elevated cortisol and prolactin levels, accompanied by reduced cholesterol and triglyceride levels. These observations indicated that premature lactation in the heifers could be associated with transport-induced stress, hormonal imbalances, and potential zearalenone contamination in the feed. Interventions were implemented upon the appearance of clinical signs, including the reduction of artificial lighting in the barns to reduce solar-induced stress, removal of concentrate from the diet with only timothy hay retained, and implementing timely monitoring and treatment of mastitis cases. The majority of the heifers calved successfully as expected, with the exception of one premature calving case (approximately 6 weeks early). Notably, half of the heifers that experienced premature lactation exhibited reduced colostrum quality at calving post-recovery with 50% (of 20 sampled) having a %Brix value of <22, (mean %Brix value of 22.13 ± 4.20). The findings emphasize the physiological challenges associated with international cattle transport and underscore the need for research-driven strategies to improve livestock acclimatization, welfare, and management during and after transportation.